The “Rodenator”: an efficient device for controlling field mice and root voles? - Kelderer, M.; Casera, C. (2008)
Field mice (Microtus arvalis), wood mice (Apodemus sylvaticus) and root voles (Arvicola terrestis) constitute a big threat to the organic apple orchards in South Tyrol. The use of rodenticides on the fields is not allowed in organic farming. The fruit growers rely on the help of different natural predators. If populations increase, the possibility of trapping and gasifying with equipment which produces carbon monoxide and carbon dioxide remain. Both methods are problematic. Trapping requires skill and time. Gasifying is not unproblematic to the health of the user. Recently a device has been imported which is used successfully in the United States to control different soil-dwelling rodents. In the orchards of South Tyrol, various field trials were carried out to evaluate the efficacy of the ‘Rodenator’ in controlling field mice.